The development and psychometric evaluation of the Perception of Play Questionnaire for older adults. Issue 2 (1st February 2016) - Tse, Mimi Mun Yee; Kwan, Tang Shuk; Lee, Paul H.
Abstract: The objective was to develop and test the psychometric properties of the Perception of Play Questionnaire among older adults. Item generation, content validation, scale piloting for item validation, and assessment of construct validity were employed to develop the questionnaire. A 17-item Perception of Play Questionnaire was developed. Items described how older adults view play from positive and negative prospective. Satisfactory results were found for content validity. The Cronbach's alpha was .775. Correlations between perception of play and life satisfaction, happiness, and loneliness were demonstrated with statistical significance ( p < 0.05). There were significant difference in multiple linear regression for frailty to Timed Up and Go Test ( p < 0.01). The Perception of Play Questionnaire can help to understand how older people view the concept and their acceptance level of play. The data gathered using the questionnaire can aid in planning interventions to improve the health of older people.